Automated and qualitative structural evaluation of floor plans for remodeling of apartment housing - Kim, Seongah; Ryu, Hyeongmin; Kim, Jinyoung (Journal of Computational Design and Engineering, 2021)
Many floor plans are proposed during the early stage of an apartment housing remodeling project as it involves a multitude of entities with different stakes. Consequently, the process to converge the opinions per the individual's preference on an agreed remodeling floor plan becomes repetitive and time consuming. For these reasons, structural evaluation of each proposed conceptual plan is often bypassed and postponed until a finalized floor plan is determined. An automated structural evaluation application for architectural floor plans of apartment housing with the load-bearing wall system is developed on this necessity. The application reads the conceptual drawings and returns various supportive information regarding structural performance, almost instantly. The outputs from the application include the amount of removed, remaining, and new bearing walls, 3D views of each wall component overlaid on the floor plans and their dimensions, area moment of inertia (AMOI) of the walls, torsional resistance of the floor plans, and other supportive indices. For easy and intuitive communication with the users, an abstract and simple quantitative value, structural index (SI), is suggested and included as one of the outputs in the application. In order to validate the developed automated application, a case study is conducted with an ongoing remodeling project, and the results, accuracy, and processing time are compared with the conventional hand calculation method. The application is accurate with errors of less than 1.3%, while the processing speed is nearly seven times faster. With the developed application, the designers could evaluate their conceptual drawings in almost real time. In addition, the stakeholders would communicate in a more straightforward language with the outputs of the application, such as the AMOI evaluation and SI results. Consequently, it is anticipated that the decision-making process during the early stage of a remodeling project would be expedited with the help of the developed automated application.
Keywords: Apartment housings; Area moment of inertias; Automated applications; Automated floor plan evaluation; Floorplans; Load bearing walls; Plan evaluation; Remodeling; Structural evaluation; Structural indices; apartment house; automated floor plan evaluation; load-bearing wall; remodeling